Tracking the Minimum Energy Consumption for the Lighting System though Modified Extremum Seeking Method. (May 2017) - Yin, Chun; Zhou, Shiwei; Wu, Shanshan; Wang, Wei; Wei, Xiuling; Cheng, Yuhua; Huang, Xuegang
Abstract: This paper investigates how to track a minimum energy consumption in the lighting system despite of environmental variations. A hardware-in-the-loop prototype of an adaptive minimum energy usage for lighting control is developed, designed and built. A modified extremum seeking control algorithm is proposed to minimize energy usage in the lighting system, while a backstepping controller is employed to maintain a desired light level. The hardware-in-the-loop experimental results are given to show the practicality and effectiveness of the proposed control method.